2020
DOI: 10.3847/1538-3881/ab6e68
|View full text |Cite
|
Sign up to set email alerts
|

CO Gas and Dust Outbursts from Centaur 29P/Schwassmann–Wachmann

Abstract: 29P/Schwassmann Wachmann is an unusual solar system object. Originally classified as a short-period comet, it is now known as a Centaur that recently transferred to its current orbit, and may become a Jupiter Family comet. It has exhibited a dust coma for over 90 years, and regularly undergoes significant dust outbursts. Carbon monoxide is routinely detected in high amounts and is typically assumed to play a large role in generating the quiescent dust coma and outbursts. To test this hypothesis, we completed t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 71 publications
6
36
0
Order By: Relevance
“…If C/2017 K2 (PANSTARRS)'s CO production rate matches that of Hale-Bopp, then we predict that it will be detectable at infrared and mm/submm wavelengths with Q(CO) ∼ 10 28 mol s −1 (Senay & Jewitt 1994;Gunnarsson et al 2003;Paganini et al 2013;Wierzchos & Womack 2020), when it reaches m helio ∼ 7.9. Based on recent lightcurve data from COBS or Yoshida, this is likely to occur during the first half of 2021 as the comet reaches m app < 12.5 and ∆ = 8.5 au.…”
Section: Estimating Co and H 2 O Production Rates For Other Cometsmentioning
confidence: 83%
“…If C/2017 K2 (PANSTARRS)'s CO production rate matches that of Hale-Bopp, then we predict that it will be detectable at infrared and mm/submm wavelengths with Q(CO) ∼ 10 28 mol s −1 (Senay & Jewitt 1994;Gunnarsson et al 2003;Paganini et al 2013;Wierzchos & Womack 2020), when it reaches m helio ∼ 7.9. Based on recent lightcurve data from COBS or Yoshida, this is likely to occur during the first half of 2021 as the comet reaches m app < 12.5 and ∆ = 8.5 au.…”
Section: Estimating Co and H 2 O Production Rates For Other Cometsmentioning
confidence: 83%
“…Several jet features could have formed into spirals or repeating features; the orientation was such that they would have been difficult to observe from Earth. Further, Wierzchos & Womack (2020) found that outbursts of CO do not always correlate with dust.…”
Section: Possible Causes Of the Repeating Jet Featurementioning
confidence: 99%
“…For example the well known active Centaur 29P has been reported to have CO and dust outbursts that are not correlated and could be associated with multiple release mechanisms acting in parallel (Wierzchos and Womack 2020).…”
Section: Thermal Environment and Its Effect On Activity Levelsmentioning
confidence: 99%